Transformation of Human Resource Performance in the Era of AI and Technological Singularity: Innovative Strategies for Modern Management - Febri Pramudya Wardani; Eogenie Lakilaki; Nurhasanah Pasaribu; I Kadek Andika Putra Bahari; Elli Sulistyaningsih (PT PUSTAKA CENDEKIA PUBLISHER, 2025)
This research aims to examine various innovative strategies that can be implemented by organizations in utilizing artificial intelligence (AI) to improve the performance of human resources (HR) while identifying the challenges and opportunities that arise in the transformation process. The method used is a literature study with a qualitative approach. Data sources were taken from various international databases such as Scopus, Web of Science, IEEE Xplore, EBSCO Business Source Complete, Emerald Insight, and Science Direct, with a time coverage between 2019 and 2025. The results show that the success of AI-based HR transformation is highly dependent on the synergy between people and technology, an ethical system design that focuses on employee needs, and the implementation of a strategy that is structured, sustainable, and able to respond to challenges from both the technical and cultural sides of the organization. Thus, it can be concluded that the integration of AI in HR management does not simply rely on technology alone but also demands fundamental changes that are strategic, ethical, and human-centered. Several key strategies such as augmented intelligence, ethical governance, continuous intelligence systems, and employee needs-based design are potential pathways to drive overall HR performance improvement.